Pemindahan Ibu Kota Negara Ke Provinsi Kalimantan Timur Berdasarkan Analisis SWOT - Saraswati, Manda Kumoro; Adi, Emmanuel Ariananto Waluyo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Jakarta has been the country's capital city since prior to the independence of Indonesia. The enactment of Law Number 29 of 2007 concerning the Provincial Government of the Special Capital Region of Jakarta confirmed Jakarta to be the capital city of Indonesia. Many dynamics over the years, such as the issue of the capital city will sink, have caused Jakarta to be deemed no longer capable of becoming the nation's capital. The discourse of relocating the capital city since President Soekarno's administration until the Jokowi administration reaffirmed on August 26, 2019, that the Government would move the State Capital from DKI Jakarta province to East Kalimantan Province. The aim is evidenced by the issuance of Law Number 3 2022 for the State Capital, ratified by the House of Representatives on January 18, 2022, and signed by President Joko Widodo on February 15, 2022. The policy to move the capital city was motivated by developing new economic areas, reducing inter-regional, and improving welfare. Based on the SWOT analysis results, the authors found that the relocation of the capital city has more strengths and opportunities than weaknesses and threats, so the relocation of the capital city is expected to impact the Indonesian economy positively.